Implementation of Independent Curriculum on Chemistry Learning Outcomes Phase E at Senior High School - Jaslin, Syafriffah; Yerimadesi, Yerimadesi (Jurnal Pijar Mipa, 2025)
This research is motivated by the Mid-Semester Summative Assessment (STS) value of chemistry phase E at State Senior High School 2 Sungai Limau of 62.60, and the correlation analysis of the implementation of the Independent Curriculum on the learning outcomes of chemistry phase E at State Senior High School 2 Sungai Limau has not been carried out. This study aims to analyze the correlation between the implementation of the Independent Curriculum and the learning outcomes of chemistry phase E at State Senior High School 2 Sungai Limau. This research is a descriptive correlational study with a mixed-method research design of the concurrent triangulation type. The research instruments used were teacher interviews, teacher teaching module reviews, teacher questionnaires, student questionnaires, and End-of-Semester Summative Assessment (SAS) documents. Data were analyzed using the Spearman Rho correlation test. The correlation coefficient value (r) obtained from the data processing results was 0.339 (positive), and the sig. value was 0.021 < 0.05, so it was in the low category. The determination coefficient value was 11.5%. Meanwhile, the other 88.5% is influenced by other variables not discussed in this study. This means that the implementation of the Independent Curriculum at State Senior High School 2 Sungai Limau has a low and significant positive correlation/relationship with the results of learning chemistry phase E. If the Independent Curriculum is implemented properly, then the results of learning chemistry can increase. The chemistry teaching modules made by teachers have begun to apply the principle of Understanding by Design (UbD). However, the chemistry teaching modules must be completed, especially in the assessment section.